2003
DOI: 10.1001/archinte.163.13.1601
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Celebrity Promotional Campaign on the Use of Colon Cancer Screening

Abstract: Katie Couric's televised colon cancer awareness campaign was temporally associated with an increase in colonoscopy use in 2 different data sets. These findings suggest that a celebrity spokesperson can have a substantial impact on public participation in preventive care programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
224
2
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(236 citation statements)
references
References 18 publications
3
224
2
5
Order By: Relevance
“…This finding is consistent with other work documenting the influence of the media on the attitudes and behaviors of the general public regarding a variety of health issues (such as low back pain, breast cancer screening, and colon cancer screening). [40][41][42] However, it is important to recognize that parents have a variety of sources of information about vaccines, including their child's physician, their family members and friends, newspapers and magazines, and the Internet. 43 Therefore, although we documented a high degree of exposure to influenza-related media stories, our data cannot determine to what degree media stories, as opposed to other sources of vaccine information, led to the changes in parental attitudes that we observed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other work documenting the influence of the media on the attitudes and behaviors of the general public regarding a variety of health issues (such as low back pain, breast cancer screening, and colon cancer screening). [40][41][42] However, it is important to recognize that parents have a variety of sources of information about vaccines, including their child's physician, their family members and friends, newspapers and magazines, and the Internet. 43 Therefore, although we documented a high degree of exposure to influenza-related media stories, our data cannot determine to what degree media stories, as opposed to other sources of vaccine information, led to the changes in parental attitudes that we observed.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Media coverage of celebrity cancer experiences has been shown to impact health service utilization and adherence to preventive health guidelines. 1,[3][4][5] The influence of celebrity health narratives differs depending on audience characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Media coverage of celebrity cancer experiences has been shown to impact health service utilization and adherence to preventive health guidelines. 1,[3][4][5] The influence of celebrity health narratives differs depending on audience characteristics. One study has shown a stronger impact of celebrity health narratives among the less educated and those who share demographic characteristics with the celebrity 6 ; another study has suggested that an emotional involvement with the celebrity may be influential.…”
Section: Introductionmentioning
confidence: 99%
“…Health-care providers often view media representations as a significant driver of patient interest in genetic testing. 4 We have seen that on issues such as cosmetic surgery 12 and cancer screening, 13 celebrities have had a significant impact on individual health-related decisions. A study about cancer reporting in Australian TV news has found that celebrities appear central to news coverage of specific cancers, especially breast cancer, which is the most reported cancer on television.…”
mentioning
confidence: 99%